Analysis of Gold Pawn in Indonesia: A Comparative Study between DSN-MUI and AAOIFI - Muna, Izzatul (University of Darussalam Gontor Press, 2024)
The development of sharia-based products in Indonesia have been increasingly rife, one of the most growing is rahn/Islamic pawn. Basically, a pawn contract is a type of tabarru’/voluntary contract which does not generate profit, however there are many Islamic financial institutions that offer pawn products especially gold pawn product. This research aims to analyze the comparison between the AAOIFI and DSN-MUI in the provisions regarding gold pawn contract. This research is a type of literature study using descriptive qualitative approach. The finding of research is that there are similarities and differences between both AAOIFI and DSN-MUI in the provisions regarding gold pawn contract. The most salient difference is that the Fatwa of DSN-MUI allows the Islamic financial institutions as the mortgagee to charge to the mortgagor some fees for safekeeping and maintenance of the mortgaged asset through ijarah contract, which make the gold pawn contract become profitable for the mortgagee. Unlike in the AAOIFI Shariah Standard which does not give the mortgagee a chance to obtain profit from this contract.